Towards an IPCC Atlas for comprehensive climate change risk assessments - Andrés Alegría; Elvira Poloczanska; Sina Loeschke; Katja Mintenbeck; Hans Poertner (npj Climate Action)
Abstract Climate risk assessments are crucial in quantifying and communicating risks in a clear and concise manner. In light of the rapidly proceeding climatic changes, there is a growing need for a more comprehensive integration and a more effective overview of available and relevant data that go into these assessments, particularly on the temporal and spatial dynamics of risk. In this paper, we describe the advantages, challenges and opportunities for increasing the accessibility of temporal and spatial data needed to support climate risk assessments through the development of an Intergovernmental Panel on Climate Change (IPCC) Atlas, integrated across IPCC Working Groups. We propose that using a climate risk framework to organise this Atlas will result in a more practical resource for understanding and informing risk assessments undertaken by the IPCC, and also make methodologies and results more accessible to a wider audience.